Synthesis of beta-SiC powders by the carbothermal reduction of porous SiO2-C hybrid precursors with controlled surface area - Youm, Mi Rae; Yun, Sung-Il; Choi, Sung Churl; Park, Sang Whan (ELSEVIER SCI LTD, 2020)
SiO2-C precursors with various surface areas were derived from tetraethyl orthosilicate and phenolic resin as Si and C sources, respectively, by a modified sol-gel process using the in situ precipitation of phenol resin in a prepared wet gel. The surface area of the SiO2-C precursors was varied from 20 to 175 m(2)/g by changing the C/Si molar ratio in the preform. beta-SiC powders were synthesized using carbothermal reduction in vacuum at the temperature range of 1200-1600 degrees C. The effects of the temperature and heat treatment time as well as that of the stifface area of the preform on the formation of beta-SiC powders were studied. It was determined that the formation of beta-SiC started at 1200 degrees C and was considerably promoted as the heat treatment temperature and time further increased during the carbothermal reduction of SiO2-C preforms with high surface area. When high surface area SiO2-C preforms were used, highly crystalline SiC powders were synthesized at 1600 degrees C in vacuum with a high yield of 85%.
Keywords: SILICON-CARBIDE POWDERS; SOL-GEL; CARBON; NANOWIRES